Relationship between Gadget Use, Sleep Patterns, Stress and the Incidence of Central Obesity in Adolescents in Jambi City - Solihin Sayuti; Ary Irfan (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Obesity is a condition in which the body has excess body weight as measured by several measurements. The accumulation of fat in the body's subcutaneous tissue, or under the skin, around organs, and sometimes even in the tissues of those organs, is a sign of obesity. In the last five years, the prevalence of adolescent obesity in Indonesia has almost doubled. The purpose of this study was to determine the factors associated with the incidence of central obesity in adolescents in Jambi City. This descriptive quantitative research used a cross-sectional study. In this study, the Solvin formula was used to calculate the sample size, which consisted of 96 adolescents living in the working area of ??the Putri Ayu health center in 2024. Data collection used a questionnaire. Data processing was univariate and bivariate analysis. The analysis used was chi-square. The results showed that there was no relationship between the use of gadgets (p=0.219) with the incidence of central obesity in adolescents there was a relationship between sleep patterns (p = 0.000), stress (p = 0.001) with the incidence of central obesity in adolescents in Jambi City. Factors that can cause obesity in adolescents include unhealthy eating habits, it is important to maintain a balanced diet, rich in fiber, and frequently consume fruits and vegetables